2018
DOI: 10.1111/jnc.14537
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of altered depression and dementia‐related proteins in the brains of young rats after ovariectomy

Abstract: Menopause, a risk factor for brain dysfunction in women, is characterized by neuropsychological symptoms including depression and dementia, which are closely related to alterations in different brain regions after menopause. However, little is known about the variability in pathophysiologic changes associated with menopause in the brain. Here, we observed that menopause in rats induced by bilateral ovariectomy (OVX) showed depressive and dementia-related behaviors along with neuronal loss in the prefrontal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 118 publications
(213 reference statements)
1
25
1
Order By: Relevance
“…While the basolateral amygdala is a more cortical-like structure, [41] the central amygdala is heavily populated by GABAergic medium spiny neurons. [42] Recent studies have reported increased depression-like behaviors and elevated CR expression levels in the amygdala of mice subjected to maternal separation or bilateral ovariectomy, [43,44] providing a link between depressive behaviors and amygdala CR levels.…”
Section: Discussionmentioning
confidence: 99%
“…While the basolateral amygdala is a more cortical-like structure, [41] the central amygdala is heavily populated by GABAergic medium spiny neurons. [42] Recent studies have reported increased depression-like behaviors and elevated CR expression levels in the amygdala of mice subjected to maternal separation or bilateral ovariectomy, [43,44] providing a link between depressive behaviors and amygdala CR levels.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampal proteomic analysis was conducted as previously described [21,22,24]. Brie y, the hippocampal proteins were extracted, digested and labeled by iTRAQ-6plex reagents in accordance with the manufacturer's protocol.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…Likewise, autophagy contributed to the estradiol-mediated protective effect on endotoxemiainduced multiple organ dysfunction (Chung et al 2017), overall indicating a cell type specific effect of estrogen deficiency on autophagy. In terms of the brain, there have been two in vivo reports, one demonstrating a shortand long-term ovarian hormone-dependent differential response on autophagy in the cortex-hippocampus mixture (Yao et al 2018), and the other claiming increased hippocampal autophagy following OVX (Fang et al 2018), marked by altered p62, Beclin-1, ATG5 and LC3-II protein levels. However, unlike ours, the studies did not delve into the autophagy regulation mechanism particularly in the hippocampal neurons.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…The primary female sex hormone, estrogen, activates its receptors, ERα and ERβ, and exhibits physiological functions within the brain (Mukai et al 2010, Hara et al 2015. Correspondingly, ovarian failure and estrogen deficiency, which characterize menopause in women, suppress cerebral ER levels (Qu et al 2013, Fang et al 2018 and alter neuronal functions, including cognition (Kim et al 2016, Djiogue et al 2018. Estrogen deficiency induces hippocampal apoptosis, neuronal loss (Sales et al 2010, Yazgan & Naziroglu 2017 and cognitive dysfunctions (Kim et al 2016, Djiogue et al 2018, while estradiol therapy reduces apoptosis and improves learning-memory performances (Sales et al 2010, Uzum et al 2016, Yazgan & Naziroglu 2017.…”
Section: Introductionmentioning
confidence: 99%